The use of phenylephrine to obtund oxytocin induced hypotension and tachycardia during elective caesarean section - Rumboll, Charles Knight (Department of Anaesthesia, 2017)
Background: Oxytocin causes clinically significant hypotension and tachycardia. This study examined whether the prior administration of phenylephrine obtunds these unwanted haemodynamic effects. Methods: Forty pregnant women undergoing elective caesarean section under spinal anaesthesia were randomised to receive either a 50 μg bolus of phenylephrine (Group P) or saline (Group S) immediately prior to oxytocin (3 IU over 15 seconds). Systolic blood pressure [SBP], diastolic blood pressure [DBP], mean arterial pressure [MAP] and heart rate [HR]) were recorded using a continuous non-invasive arterial pressure device. Baseline values were averaged for 20 seconds post-delivery. Between-group comparisons were made of the mean peak changes in BP and HR, and the mean percentage changes from baseline, during the 150 seconds after oxytocin administration. Results: The mean peak percentage change (SD) in SBP was -16.9% (2%) in Group P, and -19.0% (1.9%) in Group S and the estimated mean difference was 2.1% (95% CI: -3.5 to 7.8 %) and P =0.44; corresponding changes in HR were 13.5% (2.3%) and 14.0% (1.5%) and the mean estimated difference was 0.5% (95% CI -6.0 to 5%) and P=0.87. The mean percentage change from the baseline measurements during the 150 s period of measurement was greater for Group S than Group P: SBP -5.9% vs -3.4%; P =0.149; DBP -7.2% vs -1.5%, P =0.014; MAP -6.8% vs -1.5%, P =0.007; HR 2.1% vs -2.4%, P =0.033. Conclusion: Intravenous phenylephrine 50 μg immediately before 3 U oxytocin during elective caesarean section does not prevent maternal hypotension and tachycardia.